October Dedications : Selected Poetry of Mang Ke - Mang, Ke, 1950- (Jintian series of contemporary literature., 2018)
Mang Ke is a prominent Chinese poet and painter who started the underground literary journal Jintian (Today) with Bei Dao. He has published several collections of poetry in Chinese, as well as a novel and a volume of essays. October Dedications contains a chronological selection of material focusing on previously untranslated work from the early 1970s to late '80s.